Comparison of the Facial Morphologies of Identical Twins Using Three- Dimensional Photography: A Case Report - Altindis, Sedat; Hatunoğlu, Erdem; Toptan, Emine (My University, 2016)
The facial morphologies of identical twins were compared using the 3dMD three-dimensional (3D) photogrammetry system. 3D images of the faces of 27-year-old identical twins were acquired and then superimposed. The differences were shown in a color histogram generated using 3dMD Vultus software. The faces of the twins differed in the areas of the zygomatic region, lips, and cheeks. There were no prominent differences in other parts of their faces. Differences in the facial morphology of twins can be detected by superimposing 3D photogrammetry generated images and displaying the data as a color histogram.
Keywords: Mikroskopi; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp